Extending the «two-hits» hypothesis: the molecular mechanisms of RUNX1-RUNX1T1-mediated leuke mogenesis - Ilyushonak, Ilya N.; Saurytskaya, Hanna A.; Yatskov, Nikolai N.; Skakun, Viktor V.; Grinev, Vasiliy V. (Experimental Biology and Biotechnology, 2017)
The fusion oncogene RUNX1-RUNX1T1 is a main outcome of t(8;21)(q22;q22) nonhomologous translocation. To date, this oncogene is considered as one of the key drivers of acute myeloid leukemia. However, despite more than 20 years of study, the role of RUNX1-RUNX1T1 oncogene in development of leukemia still unclear. According to commonly accepted «two-hits» hypothesis, the fusion protein RUNX1-RUNX1T1 is dominant negative regulator of target genes for intact transcription factor RUNX1, the master regulator of hematopoietic differentiation. Meanwhile, current empirical data does not allow considering this hypothesis as self-sufficient in the existing form. In particularly, it was shown that the fusion oncogene RUNX1-RUNX1T1 possesses anti-leukemia activity. This oncogene can also work not only as repressor but as transcription activator as well and it needs a functional cooperation with intact RUNX1. In this review, we considered a modern data about role of RUNX1-RUNX1T1 oncogene in development of acute myeloid leukemia and we also proposed some general ideas how to improve a model of RUNX1-RUNX1T1-mediated leukemogenesis.
Keywords: acute myeloid leukemia; fusion oncogene RUNX1-RUNX1T1; the «two-hits» hypothesis